Religious Movement Figure K.H. Abdul Chalim Leuwimunding and His Role in Establishing Hizbullah Majalengka - Ratminingtyas (STAI AL-FALAH CICALENGKA, 2024)
The researcher is interested in researching and analyzing the role of K.H. Abdul Chalim Leuwimunding as one of the founders of the largest Islamic organization in Indonesia, namely Nahdlatul Ulama (NU) in its development in Majalengka Regency as his birthplace. The researcher's interest is because he was born in the same place as the researcher, namely in Leuwimunding Village, Leuwimunding District. Initially, his name was not well known, both locally and nationally. However, after being named a Hero of the Indonesian Independence Struggle as one of the founders of Nahdlatul Ulama (NU) who came from Leuwimunding District, Majalengka Regency, he became better known to the Indonesian people. He was awarded the title of National Hero of Indonesia based on Presidential Decree No. 115-TK-TH-2023 dated November 6, 2023. The main problem studied in this study is how the role of K.H. Abdul Chalim Leuwimunding in developing NU in Majalengka Regency in 1931-1972. This study uses historical methods consisting of heuristics, source criticism, interpretation, and historiography. Based on the findings of this study, K.H. Abdul Chalim Leuwimunding is a religious figure from Majalengka who was born on June 2, 1898, became one of the founders of NU in Surabaya and had a close relationship with K.H. Hasyim Asy'ari and K.H. Abdul Wahab Hasbullah by being active as the katib tsani of the early NU management in 1926-1928 until becoming a member of Latjah Nashihin which led him to become a NU mover in Majalengka Regency. The role of K.H. Abdul Chalim Leuwimunding in developing NU in Majalengka Regency can be seen from his activities which often mobilize from Surabaya to Cirebon-Majalengka in order to inform the latest developments of NU by visiting clerics and the surrounding community in Majalengka, he also became the chairman of the Cirebon branch of the NU Consul, and was active in the Majalengka and Cirebon Hizbullah troops.